PEMBERDAYAAN MASYARAKAT DESA PANDANARUM UNTUK MEWUJUDKAN SDGs EKOSISTEM DARATAN - Muhammad Reza Hudaya; Eka Zuni Lusi Astuti (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2020)
Blitar Regency has a potential terrestrial ecosystem to improve community welfare. However, the government's low commitment to manage terrestrial ecosystem can cause environmental damage. For example, damage to the terrestrial ecosystem in Pandanarum Village due to deforestation has caused natural disasters such as floods, landslides, and air temperature rise. Not only in Pandanarum village, but also the surrounding villages were also affected by the disaster. This condition led to establish an environmental-loving community called Sahabat Menanam in year 2015. Sahabat Menanam is doing some efforts to overcome the terrestrial ecosystem damage in Pandanarum through community empowerment approach. This study aims to describe the efforts of Sahabat Menanam in empowering Pandanarum community, by using qualitative methods. Data was collected through participant observation, in-depth interviews, and documentation. The study shows that Sahabat Menanam has succeeded in empowering the Pandanarum community, which is demonstrated by an independent community through increasing knowledge and capacity to conserve terrestrial ecosystems. After the community becomes an independent society, efforts to conserve terrestrial ecosystems can be carried out in a sustainable manner by community elements themselves with or without intervention from Sahabat Menanam.